2016
DOI: 10.1111/vde.12363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluralaner in 17 dogs with sarcoptic mange

Abstract: Fluralaner was effective in eliminating scabies mites within 14 days and significantly resolved the clinical signs associated with sarcoptic mange within 21 days after a single dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The efficacy of the treatment was assessed weekly by clinical lesion scores and superficial skin scrapings by the same veterinarian (on days 0, 7, 14 and 21). Clinical lesion scores were evaluated as described previously, with some modifications for raccoon dogs . Briefly, 12 body sites typically involved in S .…”
Section: Case Reportsupporting
confidence: 83%
See 2 more Smart Citations
“…The efficacy of the treatment was assessed weekly by clinical lesion scores and superficial skin scrapings by the same veterinarian (on days 0, 7, 14 and 21). Clinical lesion scores were evaluated as described previously, with some modifications for raccoon dogs . Briefly, 12 body sites typically involved in S .…”
Section: Case Reportsupporting
confidence: 83%
“…However, at Day 7 after fluralaner treatment, mites were not observed in all raccoon dogs (Table ). Although the response to fluralaner in this study was faster than that reported previously in dogs, further studies need to be performed to verify complete eradication and to optimize the appropriate dose and regimen required for the treatment of scabies in raccoon dogs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This compound was successfully used in parasitic skin diseases as miticidal therapy for sarcoptic mange (Romero et al, 2016) and demodicosis (Fourie et al, 2015;Duangkaew et al, 2018). Against generalized demodicosis, its administration resulted in 99.8% reduction of the mean mite observed by skin scrapings 28 days after treatment, while a 100% reduction was observed in 56 days after treatment (Fourie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is approved for use in dogs and cats for flea and tick prevention in the USA, and efficacy has been reported in the treatment of Demodex spp . and Sarcoptes scabiei in dogs. Fluralaner has been given to eight‐week‐old puppies at five times the recommended dose (280 mg/kg) with no adverse effects .…”
Section: Introductionmentioning
confidence: 99%